Effect of Mutations, Incentives, and Leadership Styles on Employee Performance at Perumda Air MinumTirta Bening Lontar Kota Kupang - Jefirstson Richset Riwukore; Tien Yustini; Johannis Silvester Ottemoesoe (MEC-J (Management and Economics Journal), 2022)
The research objective is specifically to obtain the results of the analysis of the effect of mutation variables, incentives, and leadership styles on employee performance partially or simultaneously. The research method uses descriptive and verification surveys, and field data collection uses questionnaires, interviews, and documentation techniques. This research is associative research, where in this study, there are related variables that can influence other variables. The population of this study was 97 employees at the Office of Perumda Air Minum Tirta Bening Lontar Kota Kupang,  taken as a saturated sample of 97 employees. Data processing using SPSS 25 analysis tools. The results show that mutations affect employee performance, there is an incentive effect on employee performance, leadership style affects to employee performance and mutations, incentives and leadership styles affect performance. The common thread of research is that mutations, incentives, and leadership styles positively and significantly affect employee performance at the Office of Perumda Air Minum Tirta Bening Lontar Kota Kupang, either partially or simultaneously.